POTENSI BIRDWATCHING SEBAGAI SALAH SATU DAYA TARIK WISATA DI DESA WISATA JATIMULYO, KECAMATAN GIRIMULYO,KABUPATEN KULON PROGO - Afif, Fuadi; Aisyianita, Revi Agustin; Hastuti, Saptin Dwi Setyo (Sekolah Tinggi Pariwisata AMPTA, 2018)
This study aims to identify the response of tourists in Jatimulyo Tourism Village towards the plan of developing birdwatching tourism. Birds have a strong attractiveness for certain groups of people, such as bird hobbies due to their diverse characteristics which have a high selling value. Jatimulyo Tourism Village is one of the tourism villages known for its bird diversity. Regarding that situation, the Jatimulyo government issued a Village Regulation (so-called Peraturan Desa or PerDes) about prohibition of hunting activities. It was already applied by sanctioning wild-life hunters, including bird hunter. However, the application of PerDes was not strong enough to protect the bird diversity. Thus, there must be alternatives program by utilizing the bird diversity to give economic advantages for the people. Birdwatching tourism is one of the alternatives and there is possibility to develop it in this village, considering this village has already been recognized as tourism village. This research was a quantitative research and employing survey with questionnaire as the instrument. There were 100 questionnaires given to the tourists in Jatimulyo Tourism Village to gather valid data. The term of birdwatching is still a foreign term for the people. The observation results show that most of the tourists had ever heard the term but did not know its meaning. However, most of the tourists were agreed with the alternative of developing this tourism village with birdwatching as one of the attractions but in one condition i.e. the tour package was not more than one day with affordable budget. They also wanted bird observation and photography as the activities of birdwatching. Furthermore, they needed professional guide to guide them along the tour. Keywords : birdwatching, avitourism, tourism, tourism village